Suppression of antitumor T cell immunity by the oncometabolite (R)-2-hydroxyglutarate - Bunse, Lukas; Pusch, Stefan; Bunse, Theresa; Sahm, Felix; Sonner, Jana K.; Deumelandt, Katrin; Uhlig, Stefanie; Keßler, Tobias; Breckwoldt, Michael O.; Meyer, Jochen; Habel, Antje; Poschet, Gernot; et al. (Nature medicine, 2018)
An oncometabolite produced by tumor cells acts as a paracrine immunosuppressant dampening antitumor T cell responses in glioma.
Gesehen am 11.07.2018